SISTEM PELATIHAN KERJA DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN DEPARTEMEN HOUSEKEEPING ASTON NATSEPA AMBON RESORT & SPA DI AMBON - Asky Rismayanati, - (2009)
This research started from the employees' achievement capability level which was low in housekeeping department of Aston Natsepa Ambon Resort & Spa. Employees are the important factor in supporting the company service quality mostly for the company moved in interest expense sector. Employees' achievement capability which is low, often causes service given is also less maximal. This research was trying to reveal how the training problem was resolved to be the solution for the company to increase its employees' achievement capability. The type of the research that used was the qualitative method and examine the validity of the data with the triangulation method, that compared the data acquired based on observation proceeds and interview proceeds with twenty housekeeping employees who were the excessive sample. From the analysis proceeds, training system that was applied in Aston Natsepa Ambon Resort & Spa having a form such training needs analysis, training designing, training conveying, and training evaluation. It had been accomplished, but it wasn't maximized yet in housekeeping department particularly for the room attendant and public area session. Besides, the sort of training had been given for the employees of housekeeping department was 70% in skill, 25% in knowledge, and 5% in attitude. Actually training form that changes the values and attitude is necessary given, and so the team building training, so that be able to build good cooperation among employees. The motivation training in routine also helps the employees to motivate themselves to join the training without being supposed to be reminded by their superior. After analyzing against the data acquired from several respondents, it could be seen that planned well training could affect the employees' achievement capability. Training was the effective solution to increase the achievement capability of room attendant and public area session, because based on observation proceeds known that there's an increasing according to housekeeping achievement capability of room attendant and public area session after joining the training program.